Chinese Students’ Experiences Transitioning from an Intensive English Program to a U.S. University - Fox, Jill (Journal of International Students, 2020)
The purpose of this study was to explore the experiences of former intensive English program (IEP) Chinese students by concurrently examining national origin, language problems, forms of capital, culture shock, and institutional programming using qualitative case study methods. The findings give us insights into the students’ sociocultural and academic transitions, which have implications for intensive English program and university recruitment, admissions, instruction, student support, and programming.